Foreword - João Andrade Peres; Mary Aizawa Kato (Journal of Portuguese Linguistics, 2004)
In the year 2000, a triennial project entitled Português Europeu e Português Brasileiro: Unidade e Diversidade na Passagem do Milénio (European and Brazilian Portuguese: Unity and Diversity at the Turn of the Millennium) was launched, which involved numerous researchers from both Portuguese and Brazilian universities. The main goal of the project was the investigation of the most salient dissimilarities between the two varieties of Portuguese under study (EP and BP, for short), in the semantic and syntactic domains, leaving aside lexical, morphological and phonological matters.